MASA PERADABAN ISLAM KHULAFAUR RASYIDIN - Ummu Aiman; Rafi'atun Najah Qomariah (Tarbawi, 2022)
In this era of modernization, many Muslims tend to overlook the rich history of Islamic civilization, particularly during the leadership of the Khulafaur Rasyidin. This period, which took place after the death of Prophet Muhammad, is of great significance and holds valuable lessons for Muslims to learn from and apply in their lives. Thus, this article aims to shed light on the civilization of the Khulafaur Rasyidin, specifically Abu Bakar ash-Shiddiq, Umar, Utsman, and Ali, and their dedication to Islamic civilization at that time. Through literature review and various references, qualitative research has been conducted to highlight the main points of this article. Firstly, the Khulafaur Rasyidin were Islamic scholars who took over the responsibilities of the Prophet in governing the state. Their leadership styles and contributions to the Islamic society differed. Abu Bakar's leadership was centralized, Umar's was democratic, Utsman's achievements included infrastructure development, and Ali's government faced challenges due to internal conflicts. It is important to understand and learn from the leadership styles and political structures of the Khulafaur Rasyidin, as it contributed to the advancement of Islamic civilization during their 30-year reign. This knowledge will allow Muslims to draw inspiration and guidance for contemporary times.